Approaching an Auschwitz survivor Holocaust testimony and its transformations - Matthaus, Jurgen, 1959- (Oxford oral history series., 2009)
Survivor testimonies are the least replaceable and most complex sources for Holocaust study & scholars often use testimonies uncritically or selectively, mining them to support generalizations. This book brings several scholars together to analyze the testimony of one Holocaust survivor, Helen 'Zippi' Spitzer Tichauer.